ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EFEKTIVITAS PENYALURAN KREDIT MODAL KERJA TERHADAP USAHA MIKRO KECIL DAN EKSISTENSI LEMBAGA KEUANGAN (Studi Bank BPR Jatim Kantor Cabang Mojokerto) - Olfianita, Firda (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This research discusses factors influencing the effectiveness of working capital loan distribution on micro and small businesses and the existence of Bank BPR Jatim of Mojokerto branch office as one of financial institutions in Indonesia. This study uses causal relationships between the independent and dependent variables. Here two models are used. The first model is for the effectiveness of the bank in distributing working capital loan, and the second model is for the bank’s existence. The first model results in that the distribution of working capital loan by the bank influences the revenue of micro and small businesses, while assistance provided by the bank and economic condition do not influence the businesses revenue. The second model indicates that the institution’s capacity and public demand influence the bank’s existence, while regulation does not influence it. The findings can be used in designing policies and strategies to improve the development of Bank BPR Jatim of Mojokerto branch office in particular and the improvement of Indonesian financial institutions in general, through which the institutions can have the capability to maintain their existence sustainably and widely and can empower business owners especially in micro and medium sector.